(3GdeQTO GdhLjR aj Ydhe JJYdb HGdcJGH GdYRjRs - (3CHh TGeI YHO GdQMef Hf ESeGYjd GdOeTbj,J (B665 (3g` s
(3ChdgG (B:s
(3CeG HYO agPG JUfja Ldjd jMJGL Edjg Cgd GdbQBf NUhUkG ef jYJfi HYde GdbQBAGJ GdSHY hdG jYQa eYfi gPg GdJSejI s
(3BNQgG (B:s
(3hGeOO MQha GdeO YfO eScf Ch geRh BNQg hddg GdMeO hGdTcQ Ydi EJeGeg s
(3HgG fXGe GdJYbjHIs
(3jTJed cjajI fRhd GdbQBf hJdGhJg hLeY GdUMGHI dg heYfi bhd GdfHis
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1655s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdHOjQi (B_ (3GdbOS s
Keywords: (3GdbQGAGJ hGdJLhjOs